2016
DOI: 10.15343/0104-7809.20164003382389
|View full text |Cite
|
Sign up to set email alerts
|

Obstinação terapêutica sob o referencial bioético da vulnerabilidade na prática da enfermagem

Abstract: A tecnologia desencadeia dilemas bioéticos, entre eles a obstinação terapêutica. E frente a esses dilemas enfermeiros priorizam avanços tecnológicos aos saberes reflexivos. O objetivo da presente pesquisa foi o de compreender a percepção do enfermeiro de UTI sobre obstinação terapêutica, à luz do referencial bioético da vulnerabilidade. Como método, utilizou-se a pesquisa descritiva, análise do conteúdo de Bardin, com quatorze estudantes pós-graduandos do Curso de Especialização de uma instituição de ensino su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 11 publications
(20 reference statements)
0
7
0
17
Order By: Relevance
“…They see their present and future life plans threatened by the possibility of death (4) . At this moment the fear is confirmed, amid denial, revolt, sense of failure, fear or paralysis of all those involved (6) . Therefore, the support of the team with a receptive attitude to the caregiver, offering emotional support to the patient, is essential for them to elaborate the difficult news, the irreversibility of the disease and the guarded prognostic course (17) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They see their present and future life plans threatened by the possibility of death (4) . At this moment the fear is confirmed, amid denial, revolt, sense of failure, fear or paralysis of all those involved (6) . Therefore, the support of the team with a receptive attitude to the caregiver, offering emotional support to the patient, is essential for them to elaborate the difficult news, the irreversibility of the disease and the guarded prognostic course (17) .…”
Section: Discussionmentioning
confidence: 91%
“…It is reinforced by a culture that denies and rejects human mortality and reveals the biological dimension as the only one worthy of care. In this context, the damage experienced in the ICU environment for patients in the process of finitude is immense, as they are isolated from their family, lose their autonomy and dignity, and experience their death with stress, sadness, anxiety, suffering and pain (4,6) .…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in health have stimulated the extension of life, but the use of these technologies, in an inadequate way, can promote more suffering to the patient who is with a chronic disease and in an advanced stage. 14 It is necessary to think about the most appropriate path for the application of health services and policies, which provides safe support for these patients until the end of life. 6 The research showed that the age group with the highest prevalence of chronic diseases was between 60 and 90 years old.…”
Section: Resultsmentioning
confidence: 99%
“…21 Intensive care nurses, in turn, recognize that pain control for both patients and family is paramount, relieving suffering as well as accepting the process of death and terminality. 25 Another study, which investigated how nurses understand palliative care in elderly patients admitted to the Intensive Care Unit (ICU), identified that it is a prerequisite to provide the palliative care with quality, an emphasis on relieving pain and suffering. 26 In this regard, a study that evaluates nurses' perception of the establishment of orthothanasia in ICUs identifies that they understand that, when choosing palliative care, greater pain and suffering in patients is avoided, as long as it is expressed by their will or interpretation by a legal constituent through the living will.…”
Section: Perception Of Pain In Palliative Carementioning
confidence: 99%